Between the networks and the streets: youth organizations and collective actions during the pandemic (2020-2021) - Vázquez, Melina; Cozachcow, Alejandro (Última Década, 2021)
The article analyzes the political activism of young men and women during the COVID-19 pandemic in Argentina based on a survey about youth collective actions and organizations carried out between 2020 and 2021. The work covers three dimensions: a) the ways of processing the relations between presentiality and virtuality in the repertoires of collective action, as well as in the internal organization of the groups; b) the reconfigurations and emerging matters in the activists causes and agendas; c) the mobilization in the streets during the pandemic and the revitalization of right-wing groups questioning youths.